2010
DOI: 10.1089/cell.2010.0030
|View full text |Cite
|
Sign up to set email alerts
|

NKX6.1 Promotes PDX-1-Induced Liver to Pancreatic β-Cells Reprogramming

Abstract: Reprogramming adult mammalian cells is an attractive approach for generating cell-based therapies for degenerative diseases, such as diabetes. Adult human liver cells exhibit a high level of developmental plasticity and have been suggested as a potential source of pancreatic progenitor tissue. An instructive role for dominant pancreatic transcription factors in altering the hepatic developmental fate along the pancreatic lineage and function has been demonstrated. Here we analyze whether transcription factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 50 publications
4
53
0
Order By: Relevance
“…Specifically, continuous expression of NKX6-1 in the entire pancreatic progenitor pool significantly represses Ptf1a expression, preventing acinar cell differentiation, and favours an endocrine over a ductal cell fate choice (Schaffer et al 2010). In the post-natal pancreas, nuclear NKX6-1 expression is restricted to endocrine b-cells (Sander et al 2000), and it has been shown that induction of NKX6-1 expression in PDX1-expressing liver cells promotes endocrine cell reprogramming (Gefen-Halevi et al 2010). The presence of NEUROG3 and NKX6-1 expression in a subpopulation of ductal cells indicates that these cells have an endocrine progenitor-like phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, continuous expression of NKX6-1 in the entire pancreatic progenitor pool significantly represses Ptf1a expression, preventing acinar cell differentiation, and favours an endocrine over a ductal cell fate choice (Schaffer et al 2010). In the post-natal pancreas, nuclear NKX6-1 expression is restricted to endocrine b-cells (Sander et al 2000), and it has been shown that induction of NKX6-1 expression in PDX1-expressing liver cells promotes endocrine cell reprogramming (Gefen-Halevi et al 2010). The presence of NEUROG3 and NKX6-1 expression in a subpopulation of ductal cells indicates that these cells have an endocrine progenitor-like phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent studies have exploited the known islet transcriptional networks to transdifferentiate nonpancreatic or exocrine tissue into endocrine cells. Ectopic expression of different combinations of pancreatic transcription factors-including Pdx1, Ngn3, NeuroD, MafA, and Nkx6.1-promotes liver-to-pancreatic b-cell reprogramming Kojima et al 2003;Song et al 2007;Delisle et al 2009;Nagaya et al 2009;Gefen-Halevi et al 2010). Similarly, ectopic expression of a defined set of transcription factors in adult pancreatic acinar cells results in an acinar-to-b-cell conversion (Zhou et al 2008).…”
mentioning
confidence: 99%
“…It has been demonstrated that ectopic expression of Nkx6.1 alone is not a strong inducer of upper-hierarchy β-cell transcription factor expression, and that only upon coexpression with Pdx-1 was it capable of substantial insulin expression and glucose-responsive secretion of insulin. 150 The lack of expression of the full hierarchy of β-cell transcription factors makes Nkx6.1 a mediocre choice for the generation of artificial β-cells for analysis in animal models of diabetes.…”
Section: 144mentioning
confidence: 99%